(untitled) (Bangladesh Journal of Microbiology, 2025)
This study investigated the prevalence of Listeria spp. in Bangladesh and determined their hemolytic activity. A total of 103 samples, including cattle farm water, feed, raw milk, cow dung, and soil, were collected from 24 farms. Isolation was performed using Listeria enrichment broth and selective agar, followed by polymerase chain reaction (PCR) confirmation targeting the prs gene. Hemolytic activity of the isolates was determined using 5% sheep blood agar. Results reveal that the geographic location had a significant impact on the prevalence, with Sylhet division displaying the highest prevalence and Rangpur showing no presence of these pathogens. However, the sample type did not have any association with prevalence. A statistically significant correlation was found between the presence of Listeria spp. with elevated levels of fecal coliforms, suggesting common environmental or contamination sources. Investigation of the virulence potential of the Listeria isolates based on their hemolytic pattern on blood agar demonstrated that 1 of 2 of the Listeria spp. from soil samples were â-hemolytic, while no â-hemolysis was observed among isolates from cattle farm water, and cattle feed samples. The highest diversity of hemolysis patterns was observed for isolates from raw milk (Shannon index = 1.10, Simpson index = 3.00) and cow dung (Shannon index = 0.94, Simpson index = 2.36). Isolates from cattle feed samples showed the lowest diversity (Shannon index = 0.50, Simpson index = 1.47). In case of divisions, Dhaka showed the highest diversity (Shannon index = 0.97, Simpson index = 2.40) while the lowest diversity was observed in Barisal (Shannon index = 0.50, Simpson index = 1.47). In conclusion, the findings indicate a significant geographical variation in Listeria prevalence and highlight the role of environmental contamination in its occurrence. These results underscore the need for improved hygiene and monitoring strategies to mitigate public health risks. Bangla. J. Microbiol. 2025, Vol. 41, P: 1-11